2014
DOI: 10.1002/nur.21609
|View full text |Cite
|
Sign up to set email alerts
|

A Multisample Model Validation of the Evidence‐Based Practice Questionnaire

Abstract: Evidence-based practice may be implemented more successfully if the barriers to its implementation have been previously identified. Many of the available instruments to measure these barriers have been validated in single samples or without confirmatory analyses. The objective of the study was to contrast the goodness of fit of two measurement models (24 items and 19 items) for the Spanish version of the Evidence-Based Practice Questionnaire (EBPQ) in a sample of 1,673 full-time registered nurses in 10 hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Since CFA is preferred over EFA in the COSMIN methodology [ 31 ], only the results of CFA were rated in studies where both EFA and CFA were conducted. The quality of structural validity testing was rated as “very good” in 33 studies [ 36 38 , 40 , 42 44 , 47 , 49 , 50 , 53 , 55 , 72 , 74 , 75 , 77 , 79 81 , 84 , 86 , 88 , 90 , 92 , 94 , 97 – 100 , 105 , 106 , 110 ], “adequate” in 19 studies [ 39 , 45 , 48 , 51 , 52 , 57 , 58 , 60 , 62 , 69 , 76 , 89 , 91 , 95 , 108 , 109 , 111 ], “doubtful” in 9 studies [ 46 , 56 , 59 , 61 , 63 , 83 , 102 ], and as “inadequate” in two studies [ 66 , 73 ]. In both cases inadequate ratings were given due to low sample sizes [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since CFA is preferred over EFA in the COSMIN methodology [ 31 ], only the results of CFA were rated in studies where both EFA and CFA were conducted. The quality of structural validity testing was rated as “very good” in 33 studies [ 36 38 , 40 , 42 44 , 47 , 49 , 50 , 53 , 55 , 72 , 74 , 75 , 77 , 79 81 , 84 , 86 , 88 , 90 , 92 , 94 , 97 – 100 , 105 , 106 , 110 ], “adequate” in 19 studies [ 39 , 45 , 48 , 51 , 52 , 57 , 58 , 60 , 62 , 69 , 76 , 89 , 91 , 95 , 108 , 109 , 111 ], “doubtful” in 9 studies [ 46 , 56 , 59 , 61 , 63 , 83 , 102 ], and as “inadequate” in two studies [ 66 , 73 ]. In both cases inadequate ratings were given due to low sample sizes [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Inconsistent results. One study met the criteria (RMSEA = 0.052) and one study did not (RMSEA = 0.64) ( ±) No grade EBPQ [ 48 53 , 55 ] EFA and CFA. Three factors/subscales.…”
Section: Resultsmentioning
confidence: 99%
“…The questionnaire was found to have acceptable time stability and internal consistency, with Cronbach’s α > 0.8 for all dimensions, considered adequate when the objective is diagnosis and classification (Carretero‐Dios & Pérez, 2007). In contrast, the original EBPQ (Upton et al, 2014) and its Spanish adaptation (EBPQ‐19; Sese‐Abad et al, 2014) have demonstrated poor reliability in the attitude dimension. External evidence of validity was also obtained for the questionnaire, which showed significant correlations with EBPQ‐19 dimensions and, as observed in other studies (Fernandez‐Dominguez et al, 2017; Ramos‐Morcillo et al, 2015), a positive relationship between questionnaire scores and hours of EBP training.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of nurses who had learnt about EBP might be larger than the study site hospitals than at other hospitals. Therefore, this sample might not represent all clinical nurses in Japan and as such, additional validation for other samples might be required (Sesé‐Abad et al, ). Further, if other nurses had less education about EBP, the distribution of the EBPQ score will be biased and this might lead to a floor effect.…”
Section: Discussionmentioning
confidence: 99%